POLITIK LUAR NEGERI PERDANA MENTERI MANMOHAN SINGH TERHADAP TERORISME DI INDIA - Atmaja, Janu Tri (Transformasi, 2015)
The research with the title ―Foreign Politic of Prime Minister Manmohan Singh on Terrorism in India‖. The minister Manmohan Singh is an actor of decision maker. Terrorism case of India is not conducted by Islamic fundamentalist group, but also Hindu fundamentalist. Mujahiddin Deccan and Mujahiddin India are Islamic-based terrorism, whereas saffron group is terrorists of Hindu fundamentalist. Terrorism cases of India caused anarchy condition both in India and South Asian regions. The terrorism occurring in India had impacts for the country itself such as a delayed achievement of national interest, threaten territorial intact and disturb domestic political condition.The research described how foreign politic of Manmohan Singh in handling terrorism. Author analyzed the problem by using international terrorism concept, theory of national interest, national security concept, regional security theory and foreign political theory. The research is a qualitative one and uses literature to obtain data. Conclusion of the research is Manmohan Singh performed his foreign politic by determining an internal policies, namely strengthen the country’s military, and external policy was bilateral and regional collaborations and military alliance.Key words: international terrorism, national interest, national security, regional security, foreign politic